Detection and characterization of Deformed Wing Virus (DWV) in apiaries with stationary and migratory management in the province of Entre Ríos, Argentina - Gonzalez, Fernanda Noemi; Raticelli, Fabricio; Ferrufino, Cecilia Gabriela; Fagundez, Guillermina Andrea; Rodriguez, Graciela Adriana; Miño, Samuel; Dus Santos, Maria Jose (Springer Nature, 2024)
In Argentina, migratory activity in search of floral diversity has become a common approach to maximizing honey production. The Entre Ríos province possesses a floral diversity that allows beekeepers to perform migratory or stationary management. Beyond the impact caused by transhumance, migratory colonies in this province start and end the season in monoculture areas. To study the effect of these practices on viral infection, we assayed for the presence, abundance and genetic characterization of the Deformed Wing Virus (DWV) in honey bees from apiaries with both types of management. In migratory apiaries, DWV was detectable in 86.2% of the colonies at the beginning of the season (September 2018), and 66% at the end of the season (March 2019). On the other hand, DWV was detected in 44.11% and 53.12% of stationary samples, at the beginning and the end of the season, respectively. Sequence analysis from migratory and stationary colonies revealed that all samples belonged to DWV-A type. The highest viral loads were detected in migratory samples collected in September. Higher DWV presence and abundance were associated with migratory management and the sampling time. Based on our findings we propose that the benefit of migration to wild flowering areas can be dissipated when the bee colonies end the season with monoculture.